2021
DOI: 10.5603/fm.a2020.0117
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effect of selenium nanoparticles on cyclophosphamide-induced hippocampal neurotoxicity in male rats: light, electron microscopic and immunohistochemical study

Abstract: This article has been peer reviewed and published immediately upon acceptance. It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
5
12
0
Order By: Relevance
“…The current study tried to elucidate the histologic changes of rat's hippocampus after postnatal exposure to acetaminophen via light microscope and it showed that hippocampal sections of rats which received 60 mg/kg/day of acetaminophen from PND 7 to PND 14 exhibited several changes in different parts of hippocampus using H and E stains including a reduction in the thickness of the pyramidal layer of Cornue Ammonis, presence of areas that are lacking of cells, presence of Ghost like cells as an indicative features of neural cell death of pyramidal cells in hippocampus, degenerated neurocytes in pyramidal layer among very few healthy cells beside clumping pyramidal cell nuclei. These findings are consistently shown in another work which suggested that these lesions were result from damage to neurons and lead to obvious reduction in the thickness of neurocytic layer (11,21,22). On the other hand, light microscopic evaluation of sections from DG region that are belonged to the rats which received 60 mg/kg /day of acetaminophen from PND 7 to PND 14 subcutaneously revealed different changes including presence of large neurons in the molecular layer, vacuolations in the granular layer of DG with features of disorganization in DG.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The current study tried to elucidate the histologic changes of rat's hippocampus after postnatal exposure to acetaminophen via light microscope and it showed that hippocampal sections of rats which received 60 mg/kg/day of acetaminophen from PND 7 to PND 14 exhibited several changes in different parts of hippocampus using H and E stains including a reduction in the thickness of the pyramidal layer of Cornue Ammonis, presence of areas that are lacking of cells, presence of Ghost like cells as an indicative features of neural cell death of pyramidal cells in hippocampus, degenerated neurocytes in pyramidal layer among very few healthy cells beside clumping pyramidal cell nuclei. These findings are consistently shown in another work which suggested that these lesions were result from damage to neurons and lead to obvious reduction in the thickness of neurocytic layer (11,21,22). On the other hand, light microscopic evaluation of sections from DG region that are belonged to the rats which received 60 mg/kg /day of acetaminophen from PND 7 to PND 14 subcutaneously revealed different changes including presence of large neurons in the molecular layer, vacuolations in the granular layer of DG with features of disorganization in DG.…”
Section: Discussionsupporting
confidence: 82%
“…Dehydration (by serial dilution of ethyl alcohol), clearing (by xylol), and paraffin embedding of specimens were performed. Parasagittal sections of five microns (μm) were taken for all blocks to be ready for H&E staining (19)(20)(21) to be ready for blinded examination under Bright field Olympus light microscope(Japan)light microscope. The photomicrographs of structural changes were obtained by digital camera attached via plan apochromatic objectives.…”
Section: Study Ending and Histopathological Assessmentmentioning
confidence: 99%
“…Although no previous reports have examined the effects of PDGs, either alone or combined with SeNPs, on GFAP expression in brain tissue, Se and SeNPs were found to dampen apoptotic cell death processes in the hippocampus, increase GFAP expression, reduce reactive astrogliosis, increase neuronal survival, and mitigate overall neuronal damage. 85 , 108 …”
Section: Discussionmentioning
confidence: 99%
“…SeNPs have been reported to protect nerve cells from neurological disorders [ 32 ]. In this study, the influence of SeNPs on the proliferation and differentiation of NSCs was further explored.…”
Section: Resultsmentioning
confidence: 99%